2015
DOI: 10.1002/pip.2610
|View full text |Cite
|
Sign up to set email alerts
|

The impact of alkali elements on the degradation of CIGS solar cells

Abstract: Unencapsulated CIGS solar cells with high and low contents of sodium (Na) and potassium (K) were simultaneously exposed to damp heat and illumination. The solar cells with a high alkali (Na, K) content exhibited higher initial conversion efficiencies, but degraded severely within 100 h, while the alkali poor samples kept relatively stable performance under damp heat and illumination. The degradation of the samples with a high alkali content resulted in the formation of sodium rich spots on the top ZnO:Al surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 12 publications
1
57
0
Order By: Relevance
“…SIMS measurements also showed an increase in hydroxide content of one to two magnitudes in the zinc oxide layers in the H 2 O/air and H 2 O/CO 2 /N 2 samples. SIMS also indicated that the sodium profiles did not change greatly, while it has been shown to migrate under illumination or bias, leading to degradation of the solar cells [10,11]. Therefore, it is unlikely that similar reactions are occurring under these conditions.…”
Section: Discussionmentioning
confidence: 93%
“…SIMS measurements also showed an increase in hydroxide content of one to two magnitudes in the zinc oxide layers in the H 2 O/air and H 2 O/CO 2 /N 2 samples. SIMS also indicated that the sodium profiles did not change greatly, while it has been shown to migrate under illumination or bias, leading to degradation of the solar cells [10,11]. Therefore, it is unlikely that similar reactions are occurring under these conditions.…”
Section: Discussionmentioning
confidence: 93%
“…The amount of Na present in a CIGSe film is higher in films with a smaller grain size [37] and Na accumulates at the surface of the CIGSe films [6,21,38,39] and possibly in the grain boundaries [40][41][42][43].…”
Section: Sodium In Cigse Solar Cellsmentioning
confidence: 99%
“…A PDT without KF (just Se) has also been shown to significantly alter CIGS absorbers [21,22], calling into question what 'control' absorber is appropriate for KF PDT comparison. High absorber Na and K composition has also been linked to drastically accelerated degradation in photovoltaic (PV) performance [23], which undermines the industrial relevance of initial performance gains achieved with high Na and K levels. Specifically, Na and K diffused into and degraded the ZnO layer after 100 h in damp heat and light [23], underscoring the importance of understanding alkali metal bonding in CIGS.…”
Section: Introductionmentioning
confidence: 99%
“…High absorber Na and K composition has also been linked to drastically accelerated degradation in photovoltaic (PV) performance [23], which undermines the industrial relevance of initial performance gains achieved with high Na and K levels. Specifically, Na and K diffused into and degraded the ZnO layer after 100 h in damp heat and light [23], underscoring the importance of understanding alkali metal bonding in CIGS. In a departure from work utilizing KF precursors and PDTs, recent work used Cu, KF, In, and Se co-evaporation to form Cu1-xKxInSe2 (CKIS) alloys with K/(K+Cu) composition, or x, varied from 0 to 1 [24,25].…”
Section: Introductionmentioning
confidence: 99%